Survey on digital twins for Internet of Vehicles: Fundamentals, challenges, and opportunities - Jiajie Guo; Muhammad Bilal; Yuying Qiu; Cheng Qian; Xiaolong Xu; Kim-Kwang Raymond Choo (Digital Communications and Networks, 2024)
As autonomous vehicles and the other supporting infrastructures (e.g., smart cities and intelligent transportation systems) become more commonplace, the Internet of Vehicles (IoV) is getting increasingly prevalent. There have been attempts to utilize Digital Twins (DTs) to facilitate the design, evaluation, and deployment of IoV-based systems, for example by supporting high-fidelity modeling, real-time monitoring, and advanced predictive capabilities. However, the literature review undertaken in this paper suggests that integrating DTs into IoV-based system design and deployment remains an understudied topic. In addition, this paper explains how DTs can benefit IoV system designers and implementers, as well as describes several challenges and opportunities for future researchers.